2019
DOI: 10.1038/s41598-018-38241-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Supplementation of Low Dose Fluoride Alleviates Adverse Perinatal Outcomes Following Exposure to Intrauterine Inflammation

Abstract: Maternal periodontal disease has been linked to adverse pregnancy sequelae, including preterm birth (PTB); yet, root planing and scaling in pregnancy has not been associated with improved perinatal outcomes. Fluoride, a cariostatic agent, has been added to drinking water and dental products to prevent caries and improve dental health. The objective of this study was to explore the effects of fluoride supplementation using a mouse model of preterm birth and perinatal sequalae. Pregnant mice were fed low dose fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Also, oxidative stress is an inevitable component of inflammation as pro‐inflammatory cytokines activate mediators of oxidative stress which then further induce cytokines in a vicious cycle . The pro‐inflammatory cytokine response induced by intrauterine inflammation IUI) during pregnancy is thought to be a major cause of preterm birth and fetal inflammatory response syndrome FIRS), including fetal brain injury . In a recent study, our group showed that exposure to IUI leads to placental malperfusion and fetal vessel resistance, which ultimately predisposes the fetus to cardiac dysfunction and brain damage .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, oxidative stress is an inevitable component of inflammation as pro‐inflammatory cytokines activate mediators of oxidative stress which then further induce cytokines in a vicious cycle . The pro‐inflammatory cytokine response induced by intrauterine inflammation IUI) during pregnancy is thought to be a major cause of preterm birth and fetal inflammatory response syndrome FIRS), including fetal brain injury . In a recent study, our group showed that exposure to IUI leads to placental malperfusion and fetal vessel resistance, which ultimately predisposes the fetus to cardiac dysfunction and brain damage .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The pro-inflammatory cytokine response induced by 2 of 12 | YEON LEE Et aL intrauterine inflammation IUI) during pregnancy is thought to be a major cause of preterm birth and fetal inflammatory response syndrome FIRS), including fetal brain injury. 2,4,5 In a recent study, our group showed that exposure to IUI leads to placental malperfusion and fetal vessel resistance, which ultimately predisposes the fetus to cardiac dysfunction and brain damage. 6 Ultimately, this type of brain injury can lead to a spectrum of adverse neurobehavioral outcomes, such as cerebral palsy, autism, schizophrenia, and cognitive delay.…”
Section: Introductionmentioning
confidence: 99%
“…Burd et al (2010) revealed that the activation of inflammatory pathways in association with preterm birth was responsible for disrupted fetal neuronal morphology, to the exclusion of the parturition process alone. Our previous study (Jia et al., 2019) reported that LPS‐induced IUI led to neuronal cell damage in fetal brains at E18 and contributed to adverse neuromotor outcomes in offspring at postnatal day (PND) 5 and 9. The activated inflammatory environment in fetal brain may be responsible for the abnormal development of fetal brain after exposure to LPS‐induced IUI.…”
Section: Discussionmentioning
confidence: 86%
“…381 − 383 Symptoms of chronic fluoride intoxication include: (1) irritable bowel syndrome; (2) polyuria and polydipsia; (3) extreme fatigue/exhaustion/loss of muscle power; (4) insomnia; (5) low hemoglobin; (6) depression; (7) high cholesterol and high blood pressure; (8) joint pain; (9) frequent breaking of bones; (10) disabled children with bowleg, knock-knee, short stature, and mental retardation; and (11) pregnant women with anemia, low birth weight babies, preterm deliveries, intrauterine death, neonatal death, and infant mortality. 388 , 389 Some of the fluoride effects on different tissues and organs of a human body are shown in Figure 9 .…”
Section: Fluoride Toxicitymentioning
confidence: 99%